Analysis of a Fractional Order Eco-Epidemiological Model with Prey Infection and Predator Cannibalism (Journal of Nonlinear Modeling and Analysis, 2026)
This study proposes a fractional-order prey-predator model that integrates disease dynamics within prey populations, fear induced behavioral responses, and predator cannibalism. The prey population is divided into susceptible and infected classes to represent disease dynamics effectively, while predator cannibalism is modeled as a survival strategy during prey scarcity. Essential properties such as non-negativity, boundedness, and the existence and uniqueness of solutions are thoroughly examined. Stability of equilibrium points is established, and global stability is proved using Lyapunov functions. Numerical simulations validate the theoretical results, highlighting how variations in cannibalism rates and fractional-order parameters influence population dynamics and system behavior.
Keywords: Predator-prey system; Caputo fractional-order derivative; eco-epidemiological model; cannibalism; stability